2020
DOI: 10.33902/jpr.v4i1.145
|View full text |Cite
|
Sign up to set email alerts
|

The role of pre-class asynchronous online video lectures in flipped-class instruction: Identifying students perceived need satisfaction

Abstract: This study aims to develop and understand what motivates university students to use asynchronous preclass online video lectures (AOVL) for flipped classroom instruction. The study was conducted using a mixed-method research approach. A post-questionnaire survey and a focus group interview were employed in collecting qualitative data. A total of 31 respondents answered questionnaires and 10 respondents were interviewed in a focus group discussion. The quantitative result of the descriptive analysis indicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
2
14
0
1
Order By: Relevance
“…Similar qualitative studies found that the flipped-classroom approach allowed students to develop communication and team building skills (Ishak, Kurniawan, Zainuddin, & Keumala, 2020;Mason et al, 2013;Wilson, 2013). However researchers have acknowledged that the voluntary nature of qualitative data collection will not capture all student views, recognising that there are potential students who have not experienced such benefits from e-lectures (Ishak et al, 2020). Negative views were found in the current qualitative study of orthoptic students, where themes of isolation and lack of socialisation were described.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Similar qualitative studies found that the flipped-classroom approach allowed students to develop communication and team building skills (Ishak, Kurniawan, Zainuddin, & Keumala, 2020;Mason et al, 2013;Wilson, 2013). However researchers have acknowledged that the voluntary nature of qualitative data collection will not capture all student views, recognising that there are potential students who have not experienced such benefits from e-lectures (Ishak et al, 2020). Negative views were found in the current qualitative study of orthoptic students, where themes of isolation and lack of socialisation were described.…”
Section: Discussionsupporting
confidence: 50%
“…These findings reaffirm a key recommendation from this research, whereby HE institutions must seek to manage student expectations, particularly in the context of using technology and independent learning. Similar qualitative studies found that the flipped-classroom approach allowed students to develop communication and team building skills (Ishak, Kurniawan, Zainuddin, & Keumala, 2020;Mason et al, 2013;Wilson, 2013). However researchers have acknowledged that the voluntary nature of qualitative data collection will not capture all student views, recognising that there are potential students who have not experienced such benefits from e-lectures (Ishak et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…In this process, learning environments should be created for students to make their own plans, to give feedback and to improve themselves. Ishak et al (2020) says that the use of asynchronous preclass online videos in the flip-class setting had successfully promoted students' intrinsic needs based on self-determination theory perspectives, namely: perceived competence, relatedness, and autonomy. In this context, in the FLM, it can be said that pre-lesson process students have developed their self-regulation skills.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to implement the FC strategy in the learning session, lecturers must prepare and choose suitable tools and learning materials for the class, especially for the preclass and post-class activities, as the lecturer"s supervision is absent. Video is the most widely used material in FC at the preclass level [39]. The videos can be self-produced by lecturers or taken from various sources on the internet, such as YouTube.…”
Section: B Suitable Tools To Support Fc In Programmingmentioning
confidence: 99%